2020
DOI: 10.1002/mnfr.201900977
|View full text |Cite
|
Sign up to set email alerts
|

Breastmilk Lipids and Oligosaccharides Influence Branched Short‐Chain Fatty Acid Concentrations in Infants with Excessive Weight Gain

Abstract: Scope: The aim is to identify breastmilk components associated with fecal concentration of SCFAs and to investigate whether they differ between infants with high weight gain (HW) and normal weight gain (NW). Methods and results: Breastmilk and fecal samples are collected from mother-infant dyads with HW (n = 11) and NW (n = 15) at 5 and 9 months of age. Breastmilk is profiled on ultra-performance LC-quadrupole TOF-MS platform. Fecal SCFAs are quantified using an isotope-labeled chemical derivatization method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Given that maternal HMOs content and composition are known to differ by donors, [6] it is plausible that the effects seen may not extend to all milk donors of the current study. This is especially important in the clinical context where HMOs diversity, as opposed to the availability of single agents, [18,40,41] appears to mediate the protective effects against the development of NEC on individual basis. Therefore, future studies should explore the relationship between donor-specific diversity composition and host intestinal signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Given that maternal HMOs content and composition are known to differ by donors, [6] it is plausible that the effects seen may not extend to all milk donors of the current study. This is especially important in the clinical context where HMOs diversity, as opposed to the availability of single agents, [18,40,41] appears to mediate the protective effects against the development of NEC on individual basis. Therefore, future studies should explore the relationship between donor-specific diversity composition and host intestinal signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Han et al reported significantly increased fecal branched SCFAs in a patient with Type II diabetes compared to five healthy controls after UHPLC-MS/MS analysis of 12 C/ 13 C-3-NPH-derived SCFAs [ 51 ]. Using the same pretreatment method, another group identified a positive correlation between branched SCFA concentrations in infant feces and breastmilk lipid and human milk oligosaccharide (HMO) content [ 77 ]. Liebisch et al examined the pre-analytic stability of PA, AA, BA, and IBA in human feces following 3-NPH derivatization.…”
Section: Scfa Quantitation In Different Biological Matricesmentioning
confidence: 99%
“…It has been theorized that associations between human milk composition of obese mothers and child weight outcomes may be mediated by child gut microbiota [20]. As an illustrative example, Pekmez and colleagues recently found that certain breastmilk components (e.g., human milk oligosaccharide (HMO) diversity and Lacto-N-neotetraose (LNnT)) were lower in breastmilk of infants with excessive growth and that those breastmilk components were subsequently positively associated with fecal branched short-chain fatty acid (SCFA) concentrations, which may explain the rapid weight gain of these children [21]. This is an exciting future research avenue to pursue.…”
Section: Gut Microbiotamentioning
confidence: 99%